2020
DOI: 10.1136/leader-2020-000217
|View full text |Cite
|
Sign up to set email alerts
|

Developing medical leadership in India: A mission impossible?

Abstract: PurposeGlobally, there have been calls to enhance medical leadership in healthcare, although we know little about how this objective has been pursued in low-income middle-income contexts such as India. This paper highlights the opportunities to strengthen leadership in this context, while also considering the obstacles to this change and how they might be overcome.MethodsThe paper draws on a review of available secondary sources including published journal articles in the academic and grey literature, reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, in the World Economic Forum's Global Gender Pay Gap Report 2023,[38] India was ranked 127 out of 146 countries world-wide. Further, significant medical leadership competency gaps [19] exist in Indian health sector, which can be addressed through leadership development programmes [20]. India's 2017 national health policy [39] recognises this need for leadership and states that "human resource management is critical to health system strengthening and healthcare delivery ... [and it] recommends development of leadership skills …in [the] public health system."…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the World Economic Forum's Global Gender Pay Gap Report 2023,[38] India was ranked 127 out of 146 countries world-wide. Further, significant medical leadership competency gaps [19] exist in Indian health sector, which can be addressed through leadership development programmes [20]. India's 2017 national health policy [39] recognises this need for leadership and states that "human resource management is critical to health system strengthening and healthcare delivery ... [and it] recommends development of leadership skills …in [the] public health system."…”
Section: Discussionmentioning
confidence: 99%
“…To maintain research rigor and mitigate potential bias, the coding process was documented. The research findings were disseminated through workshops and blogs [24] and through checking [25] within the medical community.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This failure to public health reform has made India’s battle against COVID-19 even more difficult. We have earlier informed the presence of significant medical leadership competency gaps among doctors in India, which resulted in the under-performance of India’s major national health reforms (Gulati and Kirkpatrick, 2020). Further, to address the COVID-19 pandemic effectively, we demonstrated that leadership should be distributed across political, scientific and frontline clinical domains, with synergistic, rather than fragmented, momentum (Currie et al , 2021).…”
Section: Introductionmentioning
confidence: 99%